Structure, dynamics and roX2-lncRNA binding of tandem double-stranded RNA binding domains dsRBD1,2 of Drosophila helicase Maleless - Jagtap, Pravin Kumar Ankush; Müller, Marisa; Masiewicz, Pawel; Bülow, Sören von; Hollmann, Nele Merret; Chen, Po-Chia; Simon, Bernd; Thomae, Andreas W.; Becker, Peter B.; Hennig, Janosch (Nucleic acids symposium series, 2019)
Maleless (MLE) is an evolutionary conserved member of the DExH family of helicases in Drosophila. Besides its function in RNA editing and presumably
Gesehen am 22.10.2019